Small Molecule Mixture Analysis by Heteronuclear NMR under Spin Diffusion Conditions in Viscous DMSO–Water Solvent. Issue 20 (21st March 2017) - Lameiras, Pedro; Patis, Solène; Jakhlal, Jouda; Castex, Stéphanie; Clivio, Pascale; Nuzillard, Jean‐Marc
Abstract: Spin diffusion in NMR occurs for small‐ and medium‐sized molecules when their tumbling rate reduces in solution so that magnetization exchange by longitudinal cross relaxation becomes highly efficient. Composite DMSO–water viscous solvents were used for the first time to access the individual NMR spectra of a mixture components in spin diffusion conditions. The easy handling and high dissolution power of [D6 ]DMSO/H2 O offers a wide range of potential applications for polar and moderately apolar mixture analysis. In addition to 2D 1 H‐ 1 H NOESY and 1 H‐ 13 C HSQC‐NOESY, 1 H‐ 15 N HSQC‐NOESY, 1D and 2D 1 H‐ 19 F heteronuclear NOESY (HOESY) experiments were set up to offer new ways to individualize molecules within a mixture. This article reports the analysis of a polar mixture of four dipeptides dissolved in [D6 ]DMSO/H2 O (7:3 v/v) and that of a medium‐polarity fluorinated dinucleotide dissolved in [D6 ]DMSO/H2 O (8:2 v/v) by means of spin diffusion in NOESY, HOESY, and HSQC–NOESY experiments. Abstract : Composite DMSO–water viscous solvents were used for the first time to access the individual NMR spectra of mixture components in spin diffusion conditions. The involvement of heteronuclei such as 19 F, 15 N, and 13 C facilitated spectral interpretation.